2012
DOI: 10.1002/jmv.23347
|View full text |Cite
|
Sign up to set email alerts
|

Shift in the timing of respiratory syncytial virus circulation in a subtropical megalopolis: Implications for immunoprophylaxis

Abstract: Respiratory syncytial virus (RSV) is the most common cause of severe respiratory infections worldwide, and an important cause of childhood bronchiolitis, pneumonia and mortality. Although prevention of RSV infection by immunoprophylaxis with palivizumab has proved effective, a precise understanding of the timing of RSV outbreaks is necessary to ensure that infants are protected when RSV is circulating. In this study a consistent shift in the seasonal patterns of RSV circulation in southeast Brazil (Sao Paulo) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
1
14
0
3
Order By: Relevance
“…Climate change, in particular an increase in average annual temperature, has been hypothesized to be responsible for shortening the RSV season in England [17] . However, a shift towards earlier RSV epidemics has also been observed in São Paulo, Brazil, which cannot be attributed to changes in climate [13] . A similar shift towards later epidemics has been noted elsewhere [45] .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Climate change, in particular an increase in average annual temperature, has been hypothesized to be responsible for shortening the RSV season in England [17] . However, a shift towards earlier RSV epidemics has also been observed in São Paulo, Brazil, which cannot be attributed to changes in climate [13] . A similar shift towards later epidemics has been noted elsewhere [45] .…”
Section: Discussionmentioning
confidence: 98%
“…Most studies have found a significant association between temperature and RSV activity using time series correlation; however, the direction of the association is not consistent across studies, and such studies do not control for the temporal dependence among observations. RSV activity tends to occur in the coldest months in temperate regions where winter outbreaks are common [6] , [13] , [18] [20] , [22] , [42] and in the warmest months in subtropical and tropical climates [16] , [25] . Low absolute humidity (proportional to vapor pressure) has been found to be an important correlate of RSV activity in Spain [20] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies from subtropical climates in South America and China report an association with relatively low temperatures; however, this was not apparent in our study. This may be because the average minimum temperature on the Gold Coast does not fall as low as temperatures in these other sites [29][30][31][32][33][34]. One review of cities with similar climates found RSV activity peaked in cities when the mean temperatures were about 1-14°C in the coldest months, which is colder than the Gold Coast winter [7].…”
Section: Discussionmentioning
confidence: 99%